A generic instrument to measure customer satisfaction with the controllable elements of the in-store shopping experience - N. S. Terblanche; C. Boshoff (South African Journal of Business Management, 2006)
In this study an attempt is made to develop a generic instrument that could be used to measure customer satisfaction with the controllable elements of the in-store shopping experience. By closely following the most contemporary guidelines for scale development, and involving 11 063 respondents in four different surveys, the authors emerge with a 22-item instrument to measure satisfaction with the in-store shopping experience. The evidence of the psychometric properties of the proposed ISE instrument offered here is compelling in terms of its uni-dimensionality, with-in-method convergent validity, cross-validation of dimensions in a cross-validation sample, reliability of the instrument, its discriminant validity and its nomological validity.
Keywords: 650